Reproductive biology of long-whiskered catfish (Mystus aor) relative to temperature and precipitation from the Kaptai Lake of Bangladesh. - Shifat Ara Noor; Muhammad; Md Main Uddin Mamun; Fatema Akhter; Mst Halima Khatun; Md Mahiuddin Zahangir; Md Moudud Islam (PLoS ONE)
Life-history information is necessary for effective conservation, aquaculture development and broodstock management of fishing populations, especially for fish with significant economic exploitation. Aiming to characterise the life-history traits in relation to the environmental parameters of the long-whiskered catfish, Mystus aor, a commercially important species from Kaptai Lake, Bangladesh, different life-history data were analysed. The monthly condition factor (K) ranged from 1.15 to 1.41, and the relative condition factor (Kn) ranged from 0.14 to 0.25. The estimated relative fecundity was 18474-55504 eggs/per fish, and the maximal oocyte diameter was found in May (0.83 ± 0.11μm). The lengths at first sexual maturity (Lm) for male and female M. aor were 49.5 cm and 54.1 cm, respectively. The GSI was peaked in May for both males and females, and histological analysis also revealed the presence of yolk granules and several mature spermatids in April and May in both sexes. Analysis of environmental data over 40 years in the Kaptai lake ecosystem indicate the significant increase in the precipitation rate in spawning month which is highly correlated with the spawning season. The findings of the current study will serve as a baseline for the conservation and broodstock management in the Kaptai Lake of Bangladesh.